(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
KWT Tirto Mekar Tani uses conventional hydroponic and gallon-based vegetable cultivation methods and still uses synthetic fertilizers, which have long-term negative health impacts. Furthermore, inconsistent maintenance and limited knowledge of garden management result in limited yields, making it impossible to market more widely. Vertical vegetable cultivation using a wall planter and organic fertilizers is more effective and efficient, increasing yields, improving health, and contributing to environmental improvement. Therefore, to increase production and marketing results of organic vegetable cultivation products, community service activities include outreach, training, technology application, mentoring, and evaluation, leading to program sustainability. Human resource management training is conducted to increase business motivation, while production training covers cultivation, product processing, organic fertilizer processing, and packaging creation using Canva online. Questionnaires were administered before and after the training, which were tested on a sample of the KWT member population. The training showed an increase in the percentage of knowledge of KWT members, namely management training (6.19%; N=11), training in cultivation, processing of organic products and fertilizer (10.09%; N=16), and training in packaging design (4.3%; N=15).